The issue of developing soft skills and social maturity in the process of training future teachers and psychologists - O. V. Zabrodina; K. G. Repina (Вестник университета)
The issues of soft skills and social maturity development in the process of professional training of future teachers, artists, and psychologists have been studied. Such concepts as soft skills and social maturity have been considered, and modern publications and studies devoted to the subject have been analyzed. In modern psycho-pedagogical science different classifications of soft skills are distinguished. In the process of training there is a transfer and assimilation of theoretical knowledge, skills, and abilities, general and professional competencies formation, as well as their practical application in educational, pedagogical, industrial, and internship practice. As a result of reflection, content analysis of students’ activity products (internship report), and student surveys it has been noticed that during internship practice students-artists and partially students-psychologists face difficulties in interaction with students, parents, and employers. Social maturity is a common and important construct in interacting with others in the social and educational environment at the theoretical level of learning skills mastery, as well as in the process of realizing the professional activity of a teacher, artist, and psychologist. Activation of qualities and characteristics included in the structural composition of social maturity contributes to developing such soft skills as personal, interpersonal, and situational. Soft skills and social maturity are important in the process of education and training of future teachers and psychologists, as well as in future professional activities.